Brain and lung arteriovenous malformation rescreening practices for children and adults with hereditary hemorrhagic telangiectasia - Lauren A. Beslow; Helen Kim; Steven W. Hetts; Felix Ratjen; Marianne S. Clancy; James R. Gossage; Marie E. Faughnan (Orphanet Journal of Rare Diseases)
Abstract Background Patients with hereditary hemorrhagic telangiectasia (HHT) are at risk for organ vascular malformations including arteriovenous malformations (AVMs) in the brain and lungs. North American HHT Centers of Excellence (CoEs) routinely screen for brain and lung AVMs, with the primary goal of detecting AVMs which can be treated before complications arise. Current international HHT guidelines provide recommendations for initial screening for brain and lung AVMs among children and adults with the disease, but rescreening recommendations are not comprehensively addressed and have not been reported. We determined current rescreening practices for brain and lung AVMs for children and adults with HHT among North American HHT CoEs. Methods We surveyed North American HHT CoEs regarding rescreening practices for new brain and lung AVMs in children and adults with initial negative screening. Results All thirty CoEs responded; 28 regarding pediatric (93.3%) and 30 (100%) regarding adult HHT care. The median duration of practice experience in HHT was 11.5 (range 3–30) years for providers of pediatric HHT care and 11.5 (range 3–35) years for providers of adult HHT care. The median number of patients followed at each CoE was 60 for children (range 8–500) and 375 for adults (range 30–1500). 25/28 CoEs (89.3%) reported rescreening children for brain AVMs, most commonly with enhanced MRI (21/25, 84%). 25 CoEs rescreen children for lung AVMs, most commonly every 5 years (15/25). Only 4/30 CoEs (13.3%) rescreen adults for brain AVMs. 26/30 CoEs (86.7%) reported rescreening adults for lung AVMs, most commonly every 5 years (18/26, 69.2%). Conclusions Most HHT CoEs routinely rescreen children for brain and lung AVMs and adults for lung AVMs when initial screening is negative, but adults are infrequently rescreened for brain AVMs. Long-term data regarding risk for new brain and lung AVMs are required to establish practice guidelines for rescreening.